Mechanical and tribological properties of natural fiber reinforced epoxy composites - Behera, Sudhakar (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Mechanical and tribological properties; natural fiber; reinforced epoxy composites